Evidence and possible mechanisms of altered maximum heart rate with endurance training and tapering - Zavorsky, G. S. (Sports Medicine, 2000)
Exercise physiologists, coaches and athletes have traditionally used heart rate (HR) to monitor training intensity during exercise. While it is known that aerobic training decreases submaximal HR (HRsubmax) at a given absolute exercise workload, the general consensus is that maximum HR (HRmax) is relatively unaltered regardless of training status in a given population. It has not been seriously postulated as to whether HRmax can change modestly with aerobic training/detraining. Despite several sources stating that HRmax is unaltered with training, several studies report that HRmax is reduced following regular aerobic exercise by sedentary adults and endurance athletes, and can increase upon cessation of aerobic exercise. Furthermore, evidence suggests that tapering/detraining can increase HRmax. Therefore, it is plausible that some of the same mechanisms that affect both resting and HRsubmax may also play a role in altered HRmax. Some of the proposed mechanisms for changes in HRmax that may occur with aerobic training include autonomic (extrinsic) factors such as plasma volume expansion and(enhanced baroreflex function, while some nonautonomic (intrinsic) factors are alteration of the electrophysiology of the sinoatrial (SA) node and decreased beta-adrenergic receptor number and density. There is a high correlation between changes in both maximal oxygen uptake (VO2 max) and HRmax that occurs with training, tapering and detraining (r= -0.76: p < 0.0001; n = 314), which indicates that as VO2max improves with training, HRmax tends to decrease, and when detraining ensues, HRmax tends to increase. The overall effect of aerobic training and detraining on HRmax is moderate: effect sizes based on several studies were calculated to be -0.48 and +0.54, respectively. Therefore, analysis reveals that HRmax can be altered by 3 to 7% with aerobic training/detraining. However, because of a lack of research in the area of training on HRmax, the reader should remain speculative and allow for cautious interpretation until further, more thorough investigations are carried out as to the confirmation of mechanisms involved. Despite the limitations of using HR and HRmax as a guide to training intensity, the practical implications of monitoring changing HRmax are: (i) prescribed training intensities may be more precisely monitored; and (ii) prevention of overtraining may possibly be enhanced. As such, it may be sensible to monitor HRmax directly in athletes throughout the training year, perhaps at every macrocycle (3 to 6 weeks).